Suppose $X$ is an adapted process and $\tau_1, \ldots , \tau_k$ are stopping times such that $X^{\tau_1}, \ldots , X^{\tau_k}$ are all martingales. I want to show that then $X^{\tau_1 \vee \ldots \vee \tau_k}$ is a martingale.

Therefore, we have that \begin{align*} &X^{\tau_i} = \{X_{\tau_i \wedge t}: t \in \mathbb{R}_+ \} \qquad &&\text{w.r.t. the filtration $\{\mathcal{F}_t\}$.} \\ \text{and} \qquad &\mathbb{E}[X^{\tau_i}_t \mid \mathcal{F}_s] = X^{\tau_i}_s \qquad &&\text{for all $s < t$ and $1 \leq i \leq k$.} \end{align*} So, \begin{align*} X^{\tau_1 \vee \ldots \vee \tau_k} &= \{X_{(\tau_1 \vee \ldots \vee \tau_k) \wedge t}: t \in \mathbb{R}_+ \}\\ &= \{X_{(\tau_1 \vee t) \wedge \ldots \wedge (\tau_k\vee t)}: t \in \mathbb{R}_+ \}. \end{align*} In general, suppose $M$ is a right-continuous martingale and $\sigma$ is a stopping time. Then the stopped process $\{M_{\sigma \wedge t}: t \in \mathbb{R}_+ \}$ is a martingale w.r.t. the filtration $\{\mathcal{F}_t\}$. $(*)$

Hence, it suffices to elaborate the case $k=2$ and verify that $X^{\tau_1 \vee \tau_2}$ is indeed a martingale and then apply $(*)$ for all $k$.

However, I do not see how to write $X^{\tau_1 \vee \tau_2}$ in terms of $X^{\tau_1}$, $X^{\tau_2}$ and $X^{\tau_1 \wedge \tau_2}$.


We have $$ (\tau_1\vee\tau_2)\wedge t = (\tau_1\wedge t)\vee(\tau_2\wedge t)\\ $$ and
\begin{align} (\tau_1\wedge t)+(\tau_2\wedge t)&=(\tau_1\wedge t)\vee(\tau_2\wedge t)+(\tau_1\wedge t)\wedge(\tau_2\wedge t)\\ &=(\tau_1\wedge t)\vee(\tau_2\wedge t) + (\tau_1\wedge\tau_2\wedge t), \end{align} from which $$(\tau_1\wedge t)\vee(\tau_2\wedge t) = (\tau_1\wedge t)+(\tau_2\wedge t)-(\tau_1\wedge\tau_2\wedge t). $$ It follows that $$X_{(\tau_1\vee\tau_2)\wedge t} = X_{\tau_1\wedge t}+X_{\tau_2\wedge t}- X_{\tau_1\wedge\tau_2\wedge t}$$ and hence for $s<t$, \begin{align} \mathbb E\left[X_{(\tau_1\vee\tau_2)\wedge t}\mid\mathcal F_s\right] &= \mathbb E\left[X_{\tau_1\wedge t}\mid\mathcal F_s \right]+\mathbb E\left[X_{\tau_2\wedge t}\mid\mathcal F_s \right]-\mathbb E\left[X_{\tau_1\wedge\tau_2\wedge t}\mid\mathcal F_s \right]\\ &= X_{\tau_1\wedge s}+X_{\tau_2\wedge s}-X_{\tau_1\wedge\tau_2\wedge s}\\ &= X_{(\tau_1\vee\tau_2)\wedge s}. \end{align} This shows that $X^{\tau_1\vee\tau_2}$ is a martingale, from which the general result follows by induction.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.